Mechanism of separation and removal of water from oily sludge using liquid dimethyl ether to dissolve hydrocarbons. (September 2021) - Mu, Biao; Zhu, Wei; Zhong, Jun; Chen, Le; Lin, Naixi; Wang, Chenyu; Chen, Sipeng; Li, Zhuo
Abstract: The effective disposal of oily sludge generated from the petroleum industry has received increasing concern. The primary difficulty for the reduction and resource utilization of oily sludge is dewatering. Therefore, finding an efficient and energy-saving dewatering technology is an urgent need for the treatment of oily sludge. In this study, an innovative developed method using liquefied dimethyl ether (L-DME) for dewatering is employed to deal with oily sludge for the first time. Oily sludge from a refinery was used to conduct experiments in sequencing dissolution-separation reactors. Changes in the dehydration rate, oil recovery, group components (hydrocarbon series of petroleum, including saturates, aromatics, resins and asphaltenes) at different extraction time, temperatures and L-DME additions were measured. The results revealed that L-DME removed 90% of the water and recovered 40% of the oil, which was an amazing dehydration effect for oily sludge. The water-binding form of oily sludge is different from sewage sludge and other biomass and the water in oily sludge is in a stable water-in-oil (W/O) suspension emulsified state. L-DME was mixed with semi-colloidal like oily sludge to break the structure of the water-in-oil emulsion, making the mixture into a solid-liquid two phase substances that were easy to separate, thus achieving a high degree of separation of water. The dissolution of saturated hydrocarbons, aromatic hydrocarbons, and small amounts of colloid by L-DME played an important auxiliary role in water removal. Graphical abstract: Image 1 Highlights: L-DME method has robust dewatering ability for the oily sludge. The destruction of the W/O emulsion makes it easy to remove water. The dissolution of hydrocarbons in L-DME is the key to dehydration. This method can also efficiently recover the hydrocarbons from the oily sludge.